Perubahan Sifat Mekanik Hasil Pengelasan Gesek Aluminium 6061 Akibat Perubahan Temperatur Lingkungan - Kido, Muhammad Ikram; Sugiarto, Sugiarto; Darmadi, Djarot B. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
Friction welding is a welding technique that utilizes heat due to surface friction between a rotating and pressing workpiece. This study aims to analyze the effect of environmental temperature variations on the mechanical properties of Al 6061 alloys, friction welding specimens with variations in room temperature (27ºC), 50 ºC, 75 ºC, 100 ºC, 125 ºC, and 150 ºC. Welding is carried out using a lathe with a rotation speed of 1600 rpm, a workpiece diameter of 15 mm, a champer angle of 15º, a friction force of 65 bar for 6 seconds, and a final compressive force of 325 bar for 60 seconds. Changes in mechanical properties in terms of tensile strength and hardness. The results showed that the higher working environment temperature produced greater tensile strength than Al 6061 friction weld joints. From macro-micro observations, it was found that specimens with large tensile strength (specimens welded at 100 ºC, 125 ºC, and 150 ºC) had a large area (Zpl) and finer granules when compared to specimens with small tensile strength (specimens welded at room temperature (27 ºC), 50 ºC and 75 ºC).